EVALUASI PENERAPAN SISTEM PENGENDALIAN INTERN PENERIMAAN KAS PADA BLU RSUP PROF.DR.R.D. KANDOU MANADO - Sambeka, Tirza Melia; Sabijono, Harijanto; Runtu, Treesje (Universitas Sam Ratulangi, 2014)
Internal control system of cash receipts should be implemented as effectively as possible in a company to prevent and avoid the occurrence of errors, fraud and abuse. The purpose of this research was to evaluate the internal control conducted, to get a clear view of the internal control of cash receipts are applied to the BLU RSUP. Prof.Dr.R.D.Kandou Manado. To obtain the necessary data, the researcher used data collectors in the form of observations, interviews and documentation. Based on the results o the research, system controlling of cash receipts in the department is sufficient. But other than that, the researcher found several weakness that should be a concern of management, especially on the Entity’s documentation and the delivery of information. The writer suggested that the control has been run to date can be maintained and adapted o the conditions of the company.